Persepsi Kemudahan & Manfaat: Kunci Intensi Pengguna Maxim di Kolaka - Nur Idul Fitriani; Niar Astaginy; Hanif Kurniadi (University of Riau Kepulauan, 2026)
This study examines the impact of perceived usefulness and perceived ease of use on behavioral intentions among Maxim application users in Kolaka Regency. Using a quantitative approach, data were collected through observation, documentation, and questionnaires. The study population consists of Maxim users, with a sample of 130 respondents. Instrument testing was conducted using validity and reliability tests in SPSS 26.0, while data analysis employed measurement model testing (Outer Model) and structural model testing (Inner Model) using Smart PLS 4.0. The results indicate that perceived ease of use and perceived usefulness has a positive and significant effect on behavioral intentions